The Implementation of Legal Position Regulation of Head of Services/Agency in Local Government - Permadi Setyonagoro; Tahegga Primananda Alfath; Slamet Hari Sutanto; Galih Puji Mulyono (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2022)
The modern rule of law is a basic concept in every government activity. In the development of state administration, government activities are no longer just implementing laws as described in the trias politica concept, but also attaching the authority to make regulations, a decision that is regulating as a legal forum for policies issued. This study aims to analyze the legal position of the head of service/agency regulations that have been used in the administration of local government. The research method used is legal research with a statue approach, and a conceptual approach. The result of this research is that the regulation of the head of the service/agency does not have a position in the legislation as intended in the Act. This study is a normative juridical study, which is aimed at examining legal principles, legal systematics, research on vertical and horizontal synchronization, legal comparisons, and legal history. The result of this research is that the regulation of the head of the service/agency that administers the regional government does not have a legal position in the hierarchy of laws and regulations as regulated in the Act. Material and formal regulations of the head of service/agency are not legal products that contain rageling material. The regulation issued as a form of discretion by the head of the service/agency should only be in the form of a circular letter.